2017
DOI: 10.1113/ep086352
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of respiratory frequency and tidal volume during high‐intensity interval training

Abstract: What is the central question of this study? By manipulating recovery intensity and exercise duration during high-intensity interval training (HIIT), we tested the hypothesis that fast inputs contribute more than metabolic stimuli to respiratory frequency (f ) regulation. What is the main finding and its importance? Respiratory frequency, but not tidal volume, responded rapidly and in proportion to changes in workload during HIIT, and was dissociated from some markers of metabolic stimuli in response to both ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
87
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 43 publications
7
87
0
6
Order By: Relevance
“…Remarkably, our findings suggest the existence of a differential control of f R and V T during exercise (Nicolò et al., ), paving the way for a new series of studies specifically targeting the control of the two components of V̇E. Along these lines, we designed a study aimed at understanding how f R and V T are regulated across different exercise‐intensity domains (Nicolò, Girardi, Bazzucchi, Felici, & Sacchetti, ).…”
mentioning
confidence: 89%
“…Remarkably, our findings suggest the existence of a differential control of f R and V T during exercise (Nicolò et al., ), paving the way for a new series of studies specifically targeting the control of the two components of V̇E. Along these lines, we designed a study aimed at understanding how f R and V T are regulated across different exercise‐intensity domains (Nicolò, Girardi, Bazzucchi, Felici, & Sacchetti, ).…”
mentioning
confidence: 89%
“…An exception to this is our recent work on the differential control of f R and V T during high‐intensity exercise (Nicolò et al . ), which was inspired by previous observations (Nicolò et al . , ).…”
mentioning
confidence: 92%
“…By manipulating recovery intensity and exercise duration during high‐intensity interval training, we found that f R , unlike V T , responded rapidly and in proportion to variations in workload, and was dissociated from some markers of metabolic stimuli in response to both experimental manipulations (Nicolò et al . ). We concluded that fast inputs (including central command) appear to contribute more than metabolic stimuli to f R regulation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Given that V̇E results from an interaction between tidal volume and breathing frequency, it is interesting to speculate how each of these individual values might vary on a daily basis and what those underlying mechanisms might be. For example, breathing frequency is highly influenced by psychological stress/perception of effort (Nicolò, Marcora, & Sacchetti, ; Nicolò, Marcora, Bazzucchi, & Sacchetti, ); if we assume that tidal volume remains relatively constant for a given physical workload, a differential change in psychological stress could result in less reliable V̇E measure on a day‐to‐day basis. Additional variability that might disproportionally affect V̇E, as opposed to V̇normalO2 and V̇normalCO2, is produced by sudden transients, such as coughing, swallowing or yawning, during data collection.…”
Section: Discussionmentioning
confidence: 99%